Depression in patients with epilepsy. Pathophysiological and clinical concepts and therapeutic strategies - Paredes-Aragón, E; Ruiz-Garcia, R; Burneo, J G (Revista de neurologiá, 2023)
Depression and epilepsy are highly prevalent diseases and represent a worldwide public health problem. A non-systematic search was performed in PubMed (MEDLINE) considering current topics in pathophysiological, clinical concepts and treatment strategies in people with epilepsy and depression. Depression and epilepsy have a bidirectional relationship and share some pathophysiological substrates. Depression is the most common neuropsychiatric manifestation in epilepsy; screening and diagnosis are important to start a timely treatment. Antidepressant drugs does not increase the frequency of seizures, on the contrary, it is believed that antidepressants may help reducing the frequency of seizures. In addition, other antidepressant therapies such as Cognitive Behavioral Therapy and neuromodulation may be also effective for reducing the frequency of seizures. However the evidence regarding antidepressant treatment(s) in epilepsy is limited and further prospective studies are needed to better characterize the possible therapeutic strategies and develop standarized treatment guidelines.